Dynamics of the wing-tip vortex in the near field of a NACA 0012 aerofoil - Del-Pino-Peñas, Carlos Manuel; López-Alonso, José Manuel; Parras-Anguita, Luis; Fernández-Feria, Ramón (Cambridge University Press, 2011)
The dynamics of the wing tip vortex in the near-field of a NACA 0012 aerofoil has been analysed by means of flow visualisations in a water tunnel. Different axial distances near the wing up to four chords, Reynolds numbers up to 42,000 and three angles-of-attack are studied to characterise the behaviour of the vortex meandering. The spatio-temporal vortex centre positions show distorted elliptical shapes in a (x,y)-plane. The Reynolds number has no significant influence on the axial evolution of the meandering amplitude. In addition, the flow visualisations obtained with a low speed camera are analysed by the singular value or proper orthogonal decomposition. Thus, the most energetic displacement modes are obtained. The frequency associated to these modes is computed by FFT. In all the cases studied, our results show that the most unstable mode corresponds to the azimuthal wavenumber |n| = 1 in the so-called Kelvin helical modes and the frequency is lower or close to 1Hz.
Keywords: Movimiento de vórtices; Vórtices de estela; NACA 0012